Tubercular Prostatitis: A rare case of Genitourinary Tuberculosis - Regmi, Sunil; Acharya, Bipesh (Journal of Nobel Medical College, 2018)
Genitourinary tuberculosis is the second most common type of extra-pulmonary tuberculosis after tubercular lymphadenitis. Tuberculosis of the prostate is a relatively rare condition and most cases are diagnosed on histology following prostatectomy or prostatic biopsy. Probably several cases of tubercular prostatitis remain undiagnosed. Therefore it requires a high index of suspicion. Here we report a rare case of tubercular prostatitis in a 49 years old man who presented with features of lower urinary tract symptoms. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 65-67